Information systems in a digital transformation: contributions based on practical experiences - Ribas, Ana Inês Conceição (2021)
Nowadays, organizations face an industrial revolution, also known as Industry 4.0. In this new reality, greater digitalization is expected to come from technological potential, but also from the changes required by the business models themselves. However, since this fourth revolution is a fairly recent phenomenon, many companies wonder how to embark on these digital transformation initiatives and do it successfully. Information Systems (IS), already present in the vast majority of companies, are shown to be one of the most important pillars within the digital transformation in particular, and in the context of Industry 4.0 in general. Therefore, this work aims to explore this potential, that is, the role of IS in the digital transformation, as well as the key factors that may contribute to the successful implementation of this type of Systems within digital transformation initiatives. To answer this goal, an exploratory literature review was conducted in a first stage. Then, and based on the results of the first phase, a practical study was carried out in the context of an automotive industry company, where some digital transformation initiatives were followed. The results point to the existence of some key factors for the success of IS implementation within this type of initiatives, such as: the existence of reliable connectivity between devices, the involvement of users in each phase of the systems’ development, the analysis of existing processes, a good relationship with business partners that provide technological solutions and support them, and, also, the definition of strategic plans and roadmaps.